‘Remanika’: A short duration rice for Kuttanad, Kerala - Devika, R.; Rema Bai, N.; Leena Kumary, S. (Journal of Tropical Agriculture, 2006)
A traditional rice variety (MO 1) and three popular high yielding varieties of Kuttanad (MO 4, MO 5 and MO 6) were subjected to varying doses of gamma irradiation (10, 20 and 30 KR) in 1984 to induce mutagenesis. Our objective was to evolve mutants with high yield potential and quality, besides possessing better plant type; and selections were made accordingly. In particular, the advanced cultures were evaluated for yield, after the M6 generation. Culture M 20-19-4 (a mutant of MO 1, IET 13980) was found to be promising and it was released as ‘Remanika’ (MO 15) in 1998.